IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DALAM RANGKA PENINGKATAN RUMAH LAYAK HUNI DI KABUPATEN SIDOARJO - ardiansyah, ferdhy; Prabawati, Indah (Universitas Negeri Surabaya, 2023)
The BSPS program is one of the flagship programs of the Ministry of PUPR, as one of the efforts to deal with housing problems as a form of government concern in carrying out the construction of livable houses for MBR. The BSPS program is government facilitation in the form of a number of funds given to low-income people. The BSPS program was also carried out in Sidoarjo Regency. The purpose of this study is to describe the implementation of the Self-Help Housing Stimulant Assistance Program in increasing the availability of livable houses in Sidoarjo Regency. The approach used in this research is a qualitative approach with a descriptive research type. This study uses horn and meter implementation theory with standard indicators and policy objectives, policy resources, characteristics of implementing agents, inter-organizational communication, attitudes of implementers, economic, social and political environment. From the results of the study it was found that the implementation of the BSPS program carried out in Sidoarjo Regency had obstacles in various sectors, especially in land ownership by residents who were still in contact with PT KAI. It was also found that the BSPS program was an utilization of existing APBN funds. The utilization of the budget for implementing the BSPS program has been maximized, although there are still some obstacles. As well as in fulfilling building materials for the implementation of the BSPS program, there is a shortage of building material stocks and often the price of building materials rises. Based on the results of the research conclusions, suggestions can be given so that they are useful for implementing the BSPS program, while suggestions are as follows: there is a need for ongoing socialization regarding the BSPS program by the P2CKTR Service so that the understanding of the BSPS program can be accepted by the community and there is also a need for supervision regarding the availability of building materials and also the determination standardization of prices for building materials to prevent misuse of existing budget funds. Program BSPS menjadi salah satu program unggulan Kementerian PUPR, sebagai salah satu upaya dalam menangani masalah perumahan sebagai wujud kepedulian pemerintah dalam menyelenggarakan pembangunan rumah layak huni bagi MBR. Program BSPS adalah fasilitasi pemerintah berupa sejumlah dana yang diberikan kepada masyarakat berpenghasilan rendah. Program BSPS juga dilakukan pada Kabupaten Sidoarjo. Tujuan pada penelitian ini untuk mendeskripsikan implementasi Program Bantuan Stimulan Perumahan Swadaya dalam meningkatkan ketersediaan rumah layak huni di Kabupaten Sidoarjo. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis penelitian deskriptif. Penelitian ini menggunakan teori implementasi horn dan meter dengan indikator standar dan sasaran kebijakan, sumber daya kebijakan, karakteristik agen pelaksana, komunikasi antar organisasi, sikap para pelaksana, lingkungan ekonomi, sosial, dan politik. Dari hasil penelitian didapati bahwa implementasi program BSPS yang dilaksanakan pada Kabupaten Sidoarjo terdapat kendala diberbagai sektor terutama pada kepemilikian tanah oleh warga yang masih bersinggungan dengan PT KAI. Ditemukan juga bahwasnya program BSPS ini merupakan pemanfaatan dana APBN yang ada. Dalam pemanfaatan anggaran pelaksanaan program BSPS telah maksimal meski masih terdapat beberapa hambatan. Serta dalam pemenuhan bahan bangunan guna pelaksanaan program BSPS terdapat kekurangan stok bahan bangunan dan seringkali harga bahan bangunan naik. Berdasarkan hasil kesimpulan penelitian dapat diberikan saran agar berguna untuk pelaksanaan program BSPS, adapun saran sebagai berikut : perlu adanya sosialisasi yang berkelanjutan terkait program BSPS oleh Dinas P2CKTR agar pemahaman program BSPS dapat diterima oleh masyarakat dan juga perlu adanya pengawasan terkait ketersediaan bahan bangunan dan juga penetapan standarisasi harga bahan bangunan agar tidak terjadi penyalahgunaan dana anggaran yang ada.